A combinatorial approach to improving the performance of azoarene photoswitches - Calbo, Joaquin; Thawani, Aditya R.; Gibson, Rosina S. L.; White, Andrew J. P.; Fuchter, Matthew J. (Beilstein Journal of Organic Chemistry, 2019)
Azoarenes remain privileged photoswitches – molecules that can be interconverted between two states using light – enabling a huge range of light addressable multifunctional systems and materials. Two key innovations to improve the addressability and Z-isomer stability of the azoarenes have been ortho-substitution of the benzene ring(s) or replacement of one of the benzenes for a pyrazole (to give arylazopyrazole switches). Here we study the combination of such high-performance features within a single switch architecture. Through computational analysis and experimental measurements of representative examples, we demonstrate that ortho-benzene substitution of the arylazopyrazoles drastically increases the Z-isomer stability and allows further tuning of their addressability. This includes the discovery of new azopyrazoles with a Z-isomer thermal half-life of ≈46 years. Such results therefore define improved designs for high performance azo switches, which will allow for high precision optically addressable applications using such components.
Keywords: arylazopyrazoles; azobenzenes; molecular switches; ortho-substitution; photoswitches; thermal half-life